Development of Charity and Humanitarian Activities Through Social Networks - Maryam Asadollahi Kheirabadi, Maryam Esmaeilimotlagh, Zeinab Basiri,; Oveisi, Kaveh; Alizadeh, Fereshteh (Opción, 2019)
The current research was conducted with the aim to investigate the effect of social networks on charitable activities. This research was done using the survey method, and a questionnaire was used in order to collect data. The obtained results show that there is a relationship between different aspects of social networks with charitable activities at three levels of awareness, acceptance and implementation. The positive value r = 0.73 indicates that changes in both variables -charitable activities and social media usage- occur simultaneously. It can be concluded that this relationship is valid at the 99 % level.